Nursery rhymes for kinder times [compact disc] - Raffi; Raffi; Munroe, Lindsay (Craft Recordings, 2022)
A warm and whimsical collection of updated nursery rhymes and songs that promote kindness, empathy, and gratitude. These are not the same as the traditional nursery rhymes our parents and grandparents may have recited, many of which feel outdated and dark now.